Multicriteria optimization of cutting parameters in turning of UD-GFRP materials considering sensitivity - KENTLİ, AYKUT (SPRINGER LONDON LTD, 2009)
In this paper, a new multicriteria optimization approach is proposed for the selection of the optimal values of cutting conditions in machining. This approach aims to handle the possible manufacturing errors in design stage. These errors are taken into consideration as change in design parameters and the design most robust to change is selected as the optimum design. Machining of a glass fiber composite material is chosen in case studies. Experiments on the unidirectional glass fiber reinforced composite material are performed to investigate the effect of cutting speed, feed, and cutting depth on the cutting forces. Also, material removal rate values are obtained. Minimizing cutting forces and maximizing the material removal are considered as objectives. It is believed that the used method provides a robust way of looking at the optimum parameter selection problems.
Keywords: Machining optimization; UD-GFRP; Cutting force; Multicriteria optimization; FIBER-REINFORCED PLASTICS; SURFACE-ROUGHNESS; TOOL WEAR; COMPOSITES